Time-dependent variations in BK polyomavirus genome from kidney transplant recipients with persistent viremia - Olga Mineeva-Sangwo; Elisabet Van Loon; Graciela Andrei; Dirk Kuypers; Maarten Naesens; Robert Snoeck (Scientific Reports, 2023)
Abstract BK polyomavirus (BKPyV) is a human DNA virus that resides latent in the host’s renal tissue. Reactivation occurs occasionally and in case of kidney transplantation, it can lead to polyomavirus-associated nephropathy (PVAN). Due to the lack of specific antivirals for BKPyV and despite the risk of allograft rejection, reduction of immunosuppression remains the main approach for treating PVAN. Current data suggests that mutations can accumulate over time in the major capsid protein VP1 and can lead to neutralization escape in kidney transplant recipients. Herein, we show that mutations occur throughout the entire BKPyV genome, including in VP1. Changes were identified by per-patient comparison of viral genome sequences obtained in samples from 32 kidney recipients with persistent viremia collected at different post-transplant time-points. Amino acid changes were observed in both earlier and later post-transplant samples, although some of them were only found in later samples. Changes in VP1 mainly consisted in the introduction of a new amino acid. A switch back to the conservative amino acid was also observed. This should be considered in future approaches for treating BKPyV infection in kidney transplant recipients.